The contribution of germination functional traits to population dynamics of a desert plant community. Issue 1 (29th January 2016) - Huang, Zhenying; Liu, Shuangshuang; Bradford, Kent J.; Huxman, Travis E.; Venable, D. Lawrence
Abstract: Early life‐cycle events play critical roles in determining the population and community dynamics of plants. The ecology of seeds and their germination patterns can determine range limits, adaptation to environmental variation, species diversity, and community responses to climate change. Understanding the adaptive consequences and environmental filtering of such functional traits will allow us to explain and predict ecological dynamics. Here we quantify key functional aspects of germination physiology and relate them to an existing functional ecology framework to explain long‐term population dynamics for 13 species of desert annuals near Tucson, Arizona, USA. Our goal was to assess the extent to which germination functional biology contributes to long‐term population processes in nature. Some of the species differences in base, optimum, and maximum temperatures for germination, thermal times to germination, and base water potentials for germination were strongly related to 20‐yr mean germination fractions, 25‐yr average germination dates, seed size, and long‐term demographic variation. Comparisons of germination fraction, survival, and fecundity vs. yearly changes in population size found significant roles for all three factors, although in varying proportions for different species. Relationships between species' germination physiologies and relative germination fractions varied across years, with fast‐germinating species being favored in years with warm temperatures during rainfall events in the germination season. Species with low germination fractions and high demographic variance have low integrated water‐use efficiency, higher vegetative growth rates, and smaller, slower‐germinating seeds. We have identified and quantified a number of functional traits associated with germination biology that play critical roles in ecological population dynamics.